SISI KEMUKJIZATAN AL-QUR'AN : Kajian I’jaz Ilmi dan Tantangan Modernisasi - rosyida amalia; Muhammad Ridho; Ahmad Zainal Abidin; Nurul Hidayat; Fadila Ikke Nuralita (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
This article raises issues related to the development of increasingly sophisticated technology with the aim of making human life more flexible and enjoyable with the presence of Artificial Intelligence. The ease of accessing all work can make people forget their existence as God's perfect creatures and it is easier to deny the order that is in accordance with Kalamullah. The presence of I'jaz Ilmi is to show the greatness of the Al-Qur'an regarding the scientific facts hinted at by the Book of Allah. The method use in this paper is descriptive-qualitative-historical which prioritizes the decomposition of data based on historical sequence combined with library research. The results of this research are that the study of i'jaz ilmi based on scientific facts in the Qur'an has been proven that the book brought by Muhammad was not an encyclopedia of science, but in the centuries since the revelation of the Qur'an it has answered future problems such as the occurrence of humans originating from soil/thin which in the science of emberiology developed in 19th century. Miracles regarding scientific facts in the Qur'an provide a signal to humanity to take lessons or i'tibar.